(untitled) (Research, Society and Development, 2021)
Due to the current economic situation in the countries and the growing need to guarantee the sustainability of services, supply companies are developing techniques for the optimization of available resources. Among the several failures identified in water distribution systems, the high level of water losses stands out. This problem is being minimized by combining the sectorization of networks with pressure management. The sectorization consists of its division into smaller sectors (Measurement and Control Districts - DMC’s), in order to reduce the complexity present in the management of the network, ensuring greater reliability and improving the useful life for the pipes and devices of the system. Thus, this research aims to systematically gather scientific knowledge about the sectorization applied in water distribution networks, considering published academic articles and three databases of great relevance in the scientific literature. The methodological approach of the present work was a systematic review of the literature on the subject. A total of 37 papers were systematically identified and reviewed, through which it was possible to identify the most relevant articles. The main methodologies applied to the sectorization process are extracted, the algorithms adopted and the main benefits resulting from the application of the sectioning of the network.